Association of chemerin Rs17173608 and vaspin Rs2236242 gene polymorphisms with metabolic syndrome in Egyptian women. (2nd January 2016) - Mehanna, Eman T.; Mesbah, Noha M.; Ghattas, Maivel H.; Saleh, Samy M.; Abo-Elmatty, Dina M.
Abstract: Aim : The metabolic syndrome is a complex of interrelated risk factors for cardiovascular disease and diabetes. The adipokines, chemerin and vaspin, are known to have metabolic regulatory roles. This study aimed to assess the relation of chemerin rs17173608 and vaspin rs2236242 polymorphisms with metabolic syndrome and its related phenotypes in Egyptian women. Subjects and methods : The study included 100 healthy female subjects and 100 metabolic syndrome patients. The component traits of metabolic syndrome were determined and the genotypes of the polymorphisms were assessed using the tetra amplification refractory mutation system polymerase chain reaction procedure. Results : The minor G allele of the chemerin rs17173608 polymorphism had a significantly higher frequency in metabolic syndrome patients ( p = 0.0001). The component traits of metabolic syndrome were significantly increased in the carriers of the GG and TG genotypes. In contrast, the rare A allele of vaspin rs2236242 polymorphism was significantly higher in the control subjects ( p = 0.005). The carriers of the TA and AA genotypes showed significant relation with lower values of the phenotypes of metabolic syndrome. Conclusion : Metabolic syndrome in Egyptian females is associated with the minor allele of chemerin rs17173608 polymorphism, whereas the minor allele of vaspin rs2236242 polymorphism plays a protective role against metabolic syndrome.